PROSES PERCERAIAN DALAM PERSPEKTIF MARTIN BUBER - Imanuel Teguh Harisantoso (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
Divorce in Indonesia is increasing from time to time. This is an indisputable social fact. This research will analyze how the divorce process occurs and how a husband or wife sees their partner from Martin Buber's perspective through a philosophical approach. Divorce is a process leading to separation. Starting from a crisis and prolonged domestic conflict, in the end, it brings a new